2014
DOI: 10.1002/marc.201400332
|View full text |Cite
|
Sign up to set email alerts
|

Graphene Oxide/Carbon Nanotube Composite Hydrogels—Versatile Materials for Microbial Fuel Cell Applications

Abstract: Carbonaceous nanocomposite hydrogels are prepared with an aid of a suspension polymerization method and are used as anodes in microbial fuel cells (MFCs). (Poly N-Isopropylacrylamide) (PNIPAM) hydrogels filled with electrically conductive carbonaceous nanomaterials exhibit significantly higher MFC efficiencies than the unfilled hydrogel. The observed morphological images clearly show the homogeneous dispersion of carbon nanotubes (CNTs) and graphene oxide (GO) in the PNIPAM matrix. The complex formation of CNT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(42 citation statements)
references
References 29 publications
1
38
0
3
Order By: Relevance
“…8 At present, more and more choices have got to fabricate or modify the electrode of MFCs, with nanomaterials, nanocomposites, graphene sheet and graphene oxides owing to their high surface area, porosity and prompt electron conduction properties. [9][10][11][12][13] The results showed that the electrodes fabricated or modied by nonamaterials exhibited excellent electrochemical activity. Signicant redox peaks have found in cyclic voltammograms and electricity production of the MFCs also obtained.…”
Section: 4-6mentioning
confidence: 83%
“…8 At present, more and more choices have got to fabricate or modify the electrode of MFCs, with nanomaterials, nanocomposites, graphene sheet and graphene oxides owing to their high surface area, porosity and prompt electron conduction properties. [9][10][11][12][13] The results showed that the electrodes fabricated or modied by nonamaterials exhibited excellent electrochemical activity. Signicant redox peaks have found in cyclic voltammograms and electricity production of the MFCs also obtained.…”
Section: 4-6mentioning
confidence: 83%
“…conductivity, good chemical tolerance, and high thermal stability, which may be advantageous for the energy storage devices [33]. The current large-scale production of graphene involves the chemical exfoliation of graphite in strong acids and the resulting contains heavily oxygenated graphene sheets bearing epoxy and hydroxyl functional groups on their basal planes and carbonyl and carboxyl groups on the The aforementioned oxygen labile functional groups act as nucleation sites for the growth of nanaoparticles.…”
Section: Methodsmentioning
confidence: 99%
“…Its single atomic layer of graphite allows it to have higher electric conductivity than conventional carbon materials [33]. Despite the excellent features of graphene, there are few examples of its use in METs [34,35]. The electroactivity in stationary cells of G. sulfurreducens using graphene SPEs was also tested in this work, which resulted in a considerably increase of the signal intensity in contrast to carbon SPEs ( Figure 3B).…”
Section: Screen-printed Electrodes (Spes): Testing Electroactivity Inmentioning
confidence: 95%